The Effect of Public Investment and Governance in Enhancing MSME Growth through Investment Attractiveness - Syamsir Nur; Yusuf Yusuf; Asraf Asraf (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in regional economic development and employment creation in Indonesia. This study examines how public investment influences MSME growth through investment attractiveness and governance. Using a quantitative explanatory design, data were collected from 336 MSME actors and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that public investment has a significant direct effect on MSME growth, but its strongest effect is on investment attractiveness. Investment attractiveness significantly enhances MSME growth and serves as the dominant mediating mechanism linking public investment to business growth. Governance also contributes directly to MSME growth. However, it does not moderate the relationship between public investment and MSME growth. These findings indicate that MSME growth is driven more strongly by the improvement of regional investment attractiveness than by direct public spending alone. The study contributes to MSME and regional development literature by positioning investment attractiveness as a key transmission mechanism and governance as an independent institutional driver.  The findings suggest that local governments should design public investment as an integrated regional competitiveness strategy to strengthen infrastructure, licensing efficiency, market access, and MSME development.